The Political Economy of Global Warming - Weston, Del (Routledge, 2014)
Humanity is facing an unprecedented global catastrophe as a result of global warming. This book examines the reasons why international agencies, together with national governments, are seemingly unable to provide real and binding solutions to the problems. The reasons presented relate to the existing dominant global economic structure of capitalism as well as the fact that global warming is too often seen as an isolated problem rather than one of a suite of exceptional, converging and accelerating crises arising from the global capitalist political economy. This book adopts a political economy framework to address these issues. It accepts the science of global warming but challenges the predominant politics and economics of global warming. To illustrate the key issues involved, the book draws on South Africa – building on Samir Amin’s thesis that the country represents a microcosm of the global political economy. By taking a political economy approach, the book provides a clear explanation of the deep and pervasive problem of the denial which fails to acknowledge global warming as a systemic rather than a market problem. The book should be of interest to students and scholars researching climate change, environmental politics, environmental and ecological economics, development studies and political economics.